Islamic marriage and household studies in transition: A bibliometric review of the socio-psychological operationalization of family values - Syukroni, Fasjud; Gazali, Hidayatul Azizah; Yahya, Ahmad; Anas, Ahmad; Elfath, Silma Dianaty; Azkiyah, Ulfa Mina; Farohah, Nailil; Fahmi, A Syaiful; Lestari, Puput; Falahan, Azhar Ahmad (Research Journal in Advanced Humanities, 2026)
Purpose: This study aims to comprehensively analyze the global research landscape of Islamic marriage and family studies by examining publication trends and key contributors, mapping the intellectual structure and major thematic clusters, and identifying functional dimensions and evolutionary gaps that have emerged in response to contemporary social contexts. Methodology: This study employed a bibliometric analysis combined with a Systematic Literature Review (SLR) following PRISMA 2020 guidelines. A final dataset of 285 Scopus-indexed articles published between 2016 and 2025 was analyzed. Data were processed using VOSviewer and Biblioshiny (R package) to visualize collaboration networks and thematic evolution. Findings: The analysis revealed an exponential seventeen-fold increase in academic output, characterized by geo-epistemic hegemony centered in Southeast Asia, particularly Indonesia and Malaysia. Structurally, the field was undergoing a paradigm shift: while "Islamic Family Law" remained the central node, it became increasingly interwoven with "Mental Health" and "Conflict Resolution" clusters. From this interdisciplinary convergence, the study synthesized six core functional dimensions of Islamic marriage: spiritual, psychological, biological, economic, parenting, and social. However, evolutionary mapping exposed a persistent psycho-legal dissonance gap, wherein normative legal themes remained saturated (motor themes), while empirical instruments to measure theological constructs such as sakīnah were underdeveloped (basic themes). Originality/Value: This study is the first to quantitatively visualize the disconnection between legal formalism and the socio-psychological operationalization of family values in Islamic marriage studies. It offers a novel roadmap for bridging the gap between fiqh-based normative frameworks and the empirical realities of contemporary Muslim household resilience.